The Influence of Effective Organizational Communication affects Internal Branding Creation and Organizational Effectiveness of the Petrochemical Industry in Thailand - Thammakesorn, Thippawan; Wongsansukjaroen, Jedsada (KKBS Journal of Business Administration and Accountancy, 2020)
The purpose of the research was to study the influence of effective organizational communication and internal branding creation on organizational effectiveness. Online and offline questionnaires collected data from 400 employees of the petrochemical industries using a purposive sampling method, and 70% were supervisory. From multiple regression analysis, found; 1. The effective organizational communication factors influence organizational effectiveness. 1.1) The capability of an audience, channel, clarity, content, and creditability of communication were positive, but communication context negatively influenced the organizational goal. 1.2) Capability of audience, clarity, and communication content were a positive influence on social responsibility. 1.3) Continuity, clarity, and content of communication were a positive influence on corporate culture. 1.4) Content, continuity, audience capability, and communication channel was positive on trust in the organization. 2. effective organizational communication factors influence internal branding creation. 2.1) Continuity, the audience’s capability, channel and content of communication were positive on internal branding communications. 2.2) Continuity, content, channel and clarity of communication were positive on training side. 2.3) Clarity, channel, audience capability, and continuity of communication were positive on management support. 2.4) Continuity, content, clarity, and communication capability were positive, but communication’s credibility was negative on internal marketing activities. 2.5) Continuity, channel, context and content of communication were positive on rewording. 3. Internal branding creation factors were a positive influence on organizational effectiveness. 3.1) Internal marketing activities, internal branding communications, management support and reward were positive on organizational goal. 3.2) Internal marketing activities, management support, internal branding communications were positive on social responsibility. 3.3) Internal marketing activities, internal branding communication, management support and training were positive on corporate culture. 3.4) Internal branding communications, internal marketing activities, training and reward were positive on trust in the organization at the statistical significance level 0.05